2015
DOI: 10.1071/mf13301
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of the environmental contamination by organotins in the Gulf of Tunis: occurrence of imposex in Stramonita haemastoma (Linnaeus, 1767)

Abstract: Imposex has been observed in several regions of the world to affect many species of prosobranch gastropods such as Stramonita haemastoma (Linnaeus, 1767). This irreversible sexual anomaly is caused mainly by the accumulation of organotin compounds in tissues. The present study aimed to confirm the existence of imposex and to determine the different levels of infection in individuals of Stramonita haemastoma collected from different stations along the rocky coastline of the Gulf of Tunis. To do this, 10 station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…In fact, the use of pesticides is increased in the north and northeast sector of the country where farms and agricultural lands are concentrated [49]. Moreover, this fringe is jointly contaminated by urban discharges and hydrocarbons evacuated in harbors by transiting ships [9]. In this context, [45,51,52] reported that CAT activity was often induced by exposure to PAHs, COs and PCBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the use of pesticides is increased in the north and northeast sector of the country where farms and agricultural lands are concentrated [49]. Moreover, this fringe is jointly contaminated by urban discharges and hydrocarbons evacuated in harbors by transiting ships [9]. In this context, [45,51,52] reported that CAT activity was often induced by exposure to PAHs, COs and PCBs.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to reflect the presence of high stress suffered by these organisms. Indeed, these two zones are subject to several industrial and urban stressors and include large fishing ports with continuous maritime activity [9]. The maximal IBR values were synchronized with the minimal values of the Fulton condition factor (K), probably related to the reproductive activity of organisms during the summer and the autumn [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation